A Comparative Analysis of Technical and Vocational Education and Training (TVET) for Special Needs Students in Malaysia and Hungary - Rusli, Nor Amalina (Online Journal for TVET Practitioners, 2024)
The purpose of this article is to analyze the situation of Technical and Vocational Education and Training (TVET) for students with Special Needs in two countries-Malaysia and Hungary. This analysis will further explain the history of TVET education and the situation of special needs in both countries, apart from studying the TVET policy for students with special needs, the role of stakeholders and also the challenges of TVET education for students with special needs. A comprehensive review of the literature was carried out using scholarly databases, research papers, and policy documents. The resources priority was given to articles that focused on TVET programmes designed especially for people with special needs. This made it possible to make sure that the literature review included the most recent findings and advancements in the industry. Literature reviews and case studies have highlighted the successful revolution of TVET education for special needs individuals in Malaysia (Samuel at al., 2017). and Hungary (IBP, 2017), but it still requires more efficient measures to help these special students. As a conclusion, TVET for special needs can be seen from the highlighted areas for improvement and provides insights into the current situation by synthesizing policy documents, research studies, and theoretical frameworks. Furthermore, this comprehensive review provides information for policymakers, teachers, government and researchers working towards creating an inclusive TVET system that caters to the diverse needs of students with special needs.